Variability of basal ganglia morphology after spatial normalization: Implications for group studies - Chen, Jingyun; McKeown, Martin J.; Beg, Mirza Faisal (CMBES Proceedings, 2010)
We studied the extent of the residual anatomical variability (RAV) in groups of subjects after standard spatial normalization. The normalization performance of three Magnetic Resonance (MR) data analysis tools, Freesurfer[1], Statistical Parametric Mapping (SPM)[2], and Large Deformation Diffeomorphic Metric Mapping (LDDMM)[3] was examined when four regions of interest (ROIs) in basal ganglia in each hemisphere were considered. The data set consisted of 27 T1-weighted brain scans, from 14 Parkinson's Disease (PD) subjects and 13 age-matched control subjects. As expected, smaller ROIs had reduced Dice similarity coefficients (DSCs) when computed over all subject pairs with different group sizes and registration methods. The LDDMM method had the lowest RAV of the three methods, but was the most computationally intensive. This result has major implications for group fMRI studies that utilize spatial normalization as a standard pre-processing method, and supports the use of fMRI ROI analysis methods that compute significance in each subject’s native space, especially when basal ganglia structures are involved. Major factors that affect RAV were discussed.